096 Intraventricular migration of intraocular silicone oil. (23rd August 2021) - Edwards, Leon; Blair, Christopher; Calic, Zeljka
Abstract : Introduction: We report a case of intraventricular migration of intraocular silicone oil. Case: A 53-year-old male presented with a decreased level of consciousness. His past medical history included bilateral retinal detachment, atrial fibrillation and ischaemic stroke. Initial blood tests and chest X-ray were consistent with a community acquire pneumonia. He was started on a 5-day course of IV ceftriaxone and azithromycin with improvement in his symptoms. A CT brain was performed upon presentation given his conscious state. This demonstrated a high density in the right globe with tracking along the optic nerve and bilateral homogenous isointense spherical masses in the frontal horns of the lateral ventricles. Imaging was initially reported as bilateral vitreous haemorrhages, an optic chiasm lesion and intraventricular haemorrhage. Follow-up MRI brain confirmed the biventricular masses with evidence of a chemical shift artefact on T1 and T2 sequences. There was disappearance on the masses on fat-suppressed T1-sequences. Images were reviewed in the combined neurology-neuroradiology meeting with the diagnosis made of cerebral migration of silicone oil. Conclusion: Intraventricular migration is a rarely reported complication following intraocular silicone endotamponade. The precise mechanism of migration is unknown. As silicone appears hyperintense on CT, it can mimic a haemorrhage or mass. Cases of misidentification of intraventricular silicone have resulted in protracted hospital admissions and surgical biopsy. Typical MRI findings and a comprehensive clinical history allow for accurate identification. Early and accurate recognition is critical to avoiding unnecessary investigation and patient morbidity.